Justification of the design of the om-1a milk cooler-purifier - Dragolov, Y. (Запоріжжя : ТДАТУ, 2025)
Steamed milk has the optimal temperature for the reproduction of most microorganisms. Therefore, if it is not cooled in a timely manner, they multiply rapidly, which leads to an increase in acidity and souring of the milk.
Keywords: OM-1A; milk cooler-purifier